Micronucleus Frequencies and DNA Repair Gene XRCC3 Polymorphism in Radiation Workers of Center for Multipurpose Reactor - D. Ramadhani; Y. Lusiyanti; M. Syaifudin; S.M.H. Faradz (Atom Indonesia, 2018)
The carcinogenic effects of low radiation doses have not been fully understood until now. Studies on individuals that are occupationally exposed to low radiation doses can help to address this question. This study assesses the micronucleus (MN) frequencies as indicator of DNA damage in radiation workers that are occupationally exposed to low radiation dose. The influence of single nucleotide polymorphisms (SNPs) in XRCC3 gene on the frequency of micronuclei was also evaluated in this study. The effects of confounding factors of gender, age, and smoking status on MN frequencies was assessed in all samples. A total of 60 subjects consisting of 30 radiation workers from Center of Multipurpose Reactor (CMPR), National Nuclear Energy Agency (NNEA) of Indonesia, and 30 control samples were enrolled in this study. The results showed that the difference between MN frequency in radiation workers and in control samples was not statistically significant [0.019 vs. 0.021; p = 0.549]. Age and smoking status did not affect micronucleus frequencies in all samples (p = 0.723 and 0.828). Micronucleus frequencies in females were higher compared to males, even though the difference was not significant (p = 0.3). Radiation workers with variant alleles for XRCC3 olymorphism did not showed higher MN frequencies compared to the controls with the same genotypes. The small numbers of samples with XRCC3 variant alleles found in this study possibly contributed to the insignificant difference of MN frequencies between wild-type allele (Thr/Thr) and mutant alleles (Thr/Met or Met/Met). Further investigations using larger sample sizes and MN assay in combination with human pan-centromeric probe should be conducted to validate this study results. Other SNP in XRCC3 gene also should be evaluated to find out the association between SNP and MN frequencies.